2013
DOI: 10.1073/pnas.1221242110
|View full text |Cite
|
Sign up to set email alerts
|

Ninjurin1, a target of p53, regulates p53 expression and p53-dependent cell survival, senescence, and radiation-induced mortality

Abstract: The tumor suppressor protein p53 plays a crucial role in coordinating cellular processes, such as cell cycle arrest, apoptosis, and senescence. The nerve injury-induced protein 1 (Ninjurin1, Ninj1) is a homophilic adhesion molecule and involved in nerve regeneration. Interestingly, Ninj1 is found to be overexpressed in human cancer, but its role in tumorigenesis is not clear. Here, we found that Ninj1 is transcriptionally regulated by p53 and can be induced by DNA damage in a p53-dependent manner. We also foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 33 publications
7
50
0
Order By: Relevance
“…4F). Together, these findings indicate that Ninj1 is a potential oncogene that increases malignant characteristics of TNBC cells, in agreement with previous findings in colon cancer cells (24). To determine the role of Ninj1 in apoptosis and invasion downstream of c-Jun, we examined whether simultaneous c-Jun knockdown and Ninj1 overexpression would rescue cells from the effects of c-Jun depletion.…”
Section: Tnf␣/ap-1 Signaling Regulates Apoptosis and Cell Invasion Ansupporting
confidence: 88%
See 2 more Smart Citations
“…4F). Together, these findings indicate that Ninj1 is a potential oncogene that increases malignant characteristics of TNBC cells, in agreement with previous findings in colon cancer cells (24). To determine the role of Ninj1 in apoptosis and invasion downstream of c-Jun, we examined whether simultaneous c-Jun knockdown and Ninj1 overexpression would rescue cells from the effects of c-Jun depletion.…”
Section: Tnf␣/ap-1 Signaling Regulates Apoptosis and Cell Invasion Ansupporting
confidence: 88%
“…In line with this, up-regulation of Ninj1 expression was observed in hepatocellular carcinoma (38) and acute lymphoblastic leukemia (39). Cho et al reported that knockdown of Ninj1 suppresses cell proliferation and enhances apoptosis in human RKO colon cancer cells (24). They further demonstrated that silencing of Ninj1 increases p53 expression through modulating p53 mRNA translation in RKO cells that express wild-type p53.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, a recent paper indicated that Ninjurin1 KO mice died prematurely (21). Consistent with this result, we also observed developmental defects in some of the Ninjurin1 KO mice.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study showed that Ninjurin1 depletion promotes cell apoptosis and senescence in a p53-dependent manner (21). Although the hemogram between WT and Ninjurin1 KO mice did not differ under normal conditions (Table 1), the inflammatory EAE induction may alter the homeostatic functions of leukocytes in Ninjurin1 KO mice.…”
Section: Ninjurin1 Mutant Mice Attenuate the Susceptibility Of Mog 35mentioning
confidence: 87%